Performance of the preliminary definition of improvement in juvenile chronic arthritis patients treated with methotrexate. Issue 1 (1st January 1998) - Ruperto, Nicolino; Ravelli, Angelo; Falcini, Fernanda; Lepore, Loredana; De Sanctis, Rosetta; Zulian, Francesco; Buoncompagni, Antonella; Sardella, Maria Luisa; Strano, Ciro; Alessio, Maria; Viola, Stefania; Martini, Alberto
Abstract : OBJECTIVE: To investigate the performance of the core set of outcome measures and the preliminary definition of improvement (PDI) in the assessment of response to methotrexate (MTX) treatment in children with juvenile chronic arthritis (JCA). METHODS: Data were obtained from an open label, non-controlled trial designed to investigate the efficacy of MTX in children with JCA. All patients had the core set of variables assessed at baseline and after six months of treatment. Variables in the core set are: (1) physician global assessment of disease activity; (2) parent or patient (if appropriate in age) global assessment of overall well being; (3) functional ability; (4) number of joints with active arthritis; (5) number of joints with limited range of motion; (6) erythrocyte sedimentation rate. The PDI specifies that to be classified as improved, a patient must show at least 30% improvement from baseline in three of any six variables in the core set, with no more than one of the remaining variables worsening by more than 30%. RESULTS: A total of 111 JCA patients were included in the study. According to the PDI, after six months of MTX treatment 73 patients (66%) were classified as improved and 38 (34%) as not improved. Among the core set variables, parent assessment detected the highest percentage of patients improved (72%) and functional assessment the lowest (37%). CONCLUSION: The PDI identifies about two thirds of patients with JCA treated with low dose MTX as improved. This proportion is similar to that expected to improve based upon a previous controlled study of low dose, oral MTX and provides preliminary evidence of the definition's validity.